Profound Pathogen-Specific Alterations in Intestinal Microbiota Composition Precede Late-Onset Sepsis in Preterm Infants: A Longitudinal, Multicenter, Case-Control Study. (9th February 2021) - el Manouni el Hassani, Sofia; Niemarkt, Hendrik J; Berkhout, Daniel J C; Peeters, Carel F W; Hulzebos, Christian V; van Kaam, Anton H; Kramer, Boris W; van Lingen, Richard A; Jenken, Floor; de Boode, Willem P; Benninga, Marc A; Budding, Andries E; et al.
Abstract: Background: The role of intestinal microbiota in the pathogenesis of late-onset sepsis (LOS) in preterm infants is largely unexplored but could provide opportunities for microbiota-targeted preventive and therapeutic strategies. We hypothesized that microbiota composition changes before the onset of sepsis, with causative bacteria that are isolated later in blood culture. Methods: This multicenter case-control study included preterm infants born under 30 weeks of gestation. Fecal samples collected from the 5 days preceding LOS diagnosis were analyzed using a molecular microbiota detection technique. LOS cases were subdivided into 3 groups: gram-negative, gram-positive, and coagulase-negative S taphylococci (CoNS). Results: Forty LOS cases and 40 matched controls were included. In gram-negative LOS, the causative pathogen could be identified in at least 1 of the fecal samples collected 3 days prior to LOS onset in all cases, whereas in all matched controls, this pathogen was absent ( P = .015). The abundance of these pathogens increased from 3 days before clinical onset. In gram-negative and gram-positive LOS (except CoNS) combined, the causative pathogen could be identified in at least 1 fecal sample collected 3 days prior to LOS onset in 92% of the fecal samples, whereas these pathogens were present in 33% of the control samples ( P = .004). Overall, LOS (expect CoNS) could be predicted 1 day prior to clinical onset with an area under the curve of 0.78. Conclusions: Profound preclinical microbial alterations underline that gut microbiota is involved in the pathogenesis of LOS and has the potential as an early noninvasive biomarker. Abstract : The causative pathogen of gram-negative and gram-positive late-onset sepsis in preterm infants could be identified in fecal samples up to 3 days prior to clinical onset. Sepsis seems to originate from the gut, and microbiota could serve as a biomarker.